2014
DOI: 10.1007/s13197-014-1659-1
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and sensory characteristics of gluten-free quinoa (Chenopodium quinoa Willd)-based cookies development using an experimental mixture design

Abstract: The aim of this study was to develop a glutenfree formulation of quinoa (Chenopodium quinoa Willd.)-based cookies using experimental design of mixture to optimize a ternary mixture of quinoa flour, quinoa flakes and corn starch for parameters of colour, specific volume and hardness. Nutritional and sensory aspects of the optimized formulation were also assessed. Corn starch had a positive effect on the lightness of the cookies, but increased amounts of quinoa flour and quinoa flakes in the mixture resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 29 publications
6
53
3
2
Order By: Relevance
“…In studies carried out by Bhaduri (2013), Brito et al (2015), and Loredana, Ioan, Daniela, and Bogdan (2016), Rothschild et al (2015), a similar trend could be observed. The product with rice flour received the higher score, probably because the participants are often not familiar with gluten-free products and flours that provide great sensory changes.…”
Section: Sensory Evaluation Of Formulationssupporting
confidence: 63%
“…In studies carried out by Bhaduri (2013), Brito et al (2015), and Loredana, Ioan, Daniela, and Bogdan (2016), Rothschild et al (2015), a similar trend could be observed. The product with rice flour received the higher score, probably because the participants are often not familiar with gluten-free products and flours that provide great sensory changes.…”
Section: Sensory Evaluation Of Formulationssupporting
confidence: 63%
“…Whereas, the highest value of calcium was presented by the gluten free biscuit sample contained 40% papaya powder on contrary to control sample (242.14 and 71.96 mg/100g respectively) while, the higher values of iron content were recorded by the gluten free biscuit samples contained 10% quinoa flour plus 30% papaya powder and the gluten free biscuit sample contained 40% papaya powder with no significant differences (12.24 and 12.92 mg/100g respectively). These results were agreement with those of Brito et al (2015) they reported that the gluten-free quinoa-based cookies were found to be a good source of fiber and minerals.…”
Section: Mineral Contents Of Gluten Free Biscuit Produced From Flour supporting
confidence: 93%
“…The chemical composition of control biscuit was in agreement with those reported by Youssef (2015) he reported that wheat biscuit contained 3.75% moisture, 9.11% protein, 1.00% fiber and 77.19% total carbohydrates. Also, Brito et al (2015) reported that quinoa flour let to increase ash and fiber content and decrease the total carbohydrate content compared to the biscuit produced from wheat flour as a control. Also, these results were in agreement with those of Yusufu and Akhigbe (2014) they reported that the replacement of wheat flour by different levels of papaya powder led to increase protein, ash, fiber contents in the produced biscuit.…”
Section: Chemical Composition Of Gluten Free Biscuitmentioning
confidence: 99%
“…However, 100% quinoa flour muffin had low overall consumer acceptability due to the bitter taste of quinoa flour (Bhaduri ). An increase in quinoa supplementation (30%) also increased the hardness of cookies, which was attributed to the high content of fiber and protein (Brito and others ). The specific volume also was reduced resulting in less bulky cookies, and also the final color was darker (Brito and others ).…”
Section: Ancient Grains‐based Foodstuffs: Nutritional Added Value Andmentioning
confidence: 91%